Isolated High-Grade Malignancy of the Spinal Cord Presenting as Longitudinally Extensive Transverse Myelitis. (April 2022) - Horta, Lucas; Virmani, Deepti; Lau, K. H. Vincent; Anand, Pria
This article characterizes 2 cases of longitudinally extensive transverse myelitis (LETM) that did not respond to immunotherapy and were diagnosed by biopsy as primary central nervous system (CNS) malignancies. Diffuse H3 K27M-mutant glioma is a recently described entity with very few cases of isolated spinal disease described in adults. Primitive neuroectodermal tumor is similarly uncommon in the spinal cord. Malignancies should be considered in patients who fail to improve with immunomodulatory therapy. We believe the experiences of our center will raise awareness about that point, broaden the existing understanding of the diagnostic approach to LETM, and highlight the need for additional studies.